The Significance, Types, and Levels of Problems and Exercises in Activating Students' Cognitive Activity - Isabaeva Mashxura Muxiddinovna; Tajiboev Behzod Ghairatjon Ogli (International Journal on Integrated Education, 2022)
In this article, the ways of presenting problems and exercises based on a creative approach in teaching biology, the role, goals and tasks of the teacher's methodical competence and his/her methodical activity are highlighted.